2018
DOI: 10.3389/fcell.2018.00041
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment-Induced Non-sporadic Expression of the AXL and cKIT Receptors Are Related to Epithelial Plasticity and Drug Resistance

Abstract: The existence of rare cancer cells that sporadically acquire drug-tolerance through epigenetic mechanisms is proposed as one mechanism that drives cancer therapy failure. Here we provide evidence that specific microenvironments impose non-sporadic expression of proteins related to epithelial plasticity and drug resistance. Microarrays of robotically printed combinatorial microenvironments of known composition were used to make cell-based functional associations between microenvironments, which were design-insp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…We also observed that AXL was mainly expressed by tumor cells in contact with the stroma. A recent study shows that AXL expression is higher in collagen-I rich microenvironment [75] suggesting that the extracellular matrix could have an impact in AXL expression. In breast tumors, Gas6 is highly expressed in pre-invasive lesions associated with increased infiltrating macrophages [76].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that AXL was mainly expressed by tumor cells in contact with the stroma. A recent study shows that AXL expression is higher in collagen-I rich microenvironment [75] suggesting that the extracellular matrix could have an impact in AXL expression. In breast tumors, Gas6 is highly expressed in pre-invasive lesions associated with increased infiltrating macrophages [76].…”
Section: Discussionmentioning
confidence: 99%
“…Since MaSCs with self-renewing properties and in vivo repopulating activity are also expressed in a subpopulation of basal cells, it is tempting to speculate that Axl may be a putative stem cell marker. Indeed, Axl has been suggested to be a cancer stem cell marker [27, 28], however it is unclear as to whether Axl is a true MaSC marker in the normal mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment is a key regulator of EMP, which may be induced by combinations of multiple microenvironmental factors including hypoxia, pH, ECM composition, tensile forces and the presence of soluble factors such as interferons, inflammatory cytokines and growth factors [61,65,66,86,[96][97][98] . Hypoxia occurs in most actively growing solid tumors and is an important EMT inducer.…”
Section: The Tumor Immune Microenvironment As a Regulator Of Epithelimentioning
confidence: 99%